Description of Diplogasterid Nematodes (Nematoda: Diplogasterida) Inhabiting Syconia of Ficus Species in Haryana, India (Indian Journal of Nematology, 2024)
Examination of syconia of Ficus infectoria, F. religiosa and F. racemosa growing at Hisar, India, revealed the presence of interesting nematodes species belonging to order Diplogasterida. Teratodiplogaster racemosus n. sp.: Males: L= 1.41-2.18 mm, a= 66.5- 92.8, c=12.9-17.8, c’=6.2-7.9, right subventral metastegostom with a small, triangular tooth, dorsal metastegostom forming a cuticularplate with depression in middle, left subventral metastegostom with two denticles, seven pairs of genital papillae arranged as 1+1/1+1+Ph+ (1+1) +1D. Females: L= 1.59-2.44 mm, a= 74.7-89.1, c= 7.3-11.2, c’= 11.8-19.0, V= 46.1-51.1, Tail long, cylindrical with a centralmucro. Sigmodiplogaster religiosus n. gen., n. sp.: Medium to large-sized body. Stoma short, lateral stomal walls with rounded-conoidcuticular structures that may be bifurcated at tips. Cheilostom short, lightly cuticularized. Spicules separate, thin, slender and verylong ca one-fifth of body length long; gubernaculum made up of two parts, anterior half nearly triangular, posterior half nearly straight. Seven pairs of genital papillae, two being precloacal. Females monoprodelphic, vagina long and sigmoid. V= 63.6-70.5. Tail 1.4-1.8 bodywidths long, conoid and tapering with a mucronate tip in males and elongated conoid with a pointed tip in females. Prodelphodiplogaster infectorius n. gen., n. sp.: Medium to large-sized body. Stoma short, lateral stomal walls with rounded-conoid cuticular structures that may be bifurcated at tips. Cheilostom short, lightly cuticularized; dorsal wall of stegostom with small rounded structure. Spicules stained, separate and robust. Manubrium distinct rounded to flattened, dorsal limb arcuate, longer than ventral limb, spicular opening towards ventral side. Gubernaculum elongated and thick, proximal end thin and dorsally curved to form a hook-like structure, distal end sharply pointed. Females monoprodelphic with long post uterine sac, vagina straight. Tail about one-body-width long, conoid and tapering with a mucronate tip in males, and elongated conoid, regularly tapering to rounded pointed tip in females. Parasitodiplogaster australis Bartholomaeus et al., 2009 is transferred to this genus. Canalodiplogaster racemosus n. gen., n. sp.: Medium to large-sized body. Females polymorphic- Eurystomatous form- stegostom with movable claw-like dorsal tooth equally developed right subventral tooth; Stenostomatous form I- stegostom with mammillate dorsal and elongated subventral teeth; Stenostomatous form II with long stoma and without teeth. Females amphidelphic. Males similar to Stenostomatous form I females, Spicules very strong, arcuate. Each spicule characteristically having duct running through its whole length and ending in a gland near to manubrium. Spicule dimorphic, right spicule with broad hump like structure on dorsal limb. Left spicule with comparatively narrower hump-like structure on dorsal limb. Gubernaculum large, pouch shaped, with cuticularized blades and membranous extension. Seven pairs of genital papillae, three being precloacal. Tail elongated conoid in females and tapering abruptly beyond last pairs of genital papillae in males.